A Contextual Financial Risk Management Model for Tourism-Based MSMEs: Evidence from Carita Beach - Saefullah, Aep; Rifia, Tetty Nur Intan; Nurdin, Nurdin; Zulkarnain, Nizar; Suharjana, I Dewa Ketut (Journal of Business Management and Economic Development, 2026)
Tourism-based micro, small, and medium enterprises (MSMEs) play a crucial role in supporting local economic activities; however, they are highly exposed to financial risks due to fluctuations in tourist arrivals, weather uncertainty, and the seasonal nature of tourism destinations. This study aims to identify the types of financial risks faced by tourism-based MSMEs, examine their impact on business sustainability, and develop a practical financial risk management model suited to small-scale enterprises. A qualitative descriptive approach was employed, with data collected through in-depth interviews, direct observations, and field studies conducted during an edu-tourism program in the Carita Beach area from 1–17 December 2025. The findings reveal that the main financial risks include revenue risk, operational cost risk, and cash flow and liquidity risk. Among these, revenue instability and cash flow constraints are the most significant factors affecting business continuity, particularly during periods of declining tourist activity. MSME actors tend to manage these risks through informal, experience-based strategies such as adjusting production levels, reducing operational expenses, and relying on short-term financial coping mechanisms. This study contributes by proposing a simplified and context-based financial risk management model that aligns with the operational realities of tourism MSMEs. The model emphasizes practical risk identification, prioritization, and adaptive mitigation strategies that can be implemented without requiring complex financial systems. The findings provide implications for policymakers and practitioners in designing more inclusive and applicable financial support and risk management frameworks for tourism-based MSMEs.